Situation and needs of transgender and non-binary people in Serbia - Vidić, Jelena (Psihološka istraživanja, 2021)
Transgender and non-binary people are one of the most marginalized groups in the society exposed to different forms of violence and discrimination, both on the structural and individual level. The aim of our research is to provide a better understanding of the situation of transgender and non-binary people in Serbia. Besides overall socio-demographic characteristics, we explore experiences of violence and discrimination in public space, during education, at work; difficulties with legal gender recognition, experiences within the health care system and needs for different forms of support. In this explorative study we used an online questionnaire consisting of closed and open-ended questions. The convenience sample consists of 71 respondents and includes both transgender men and women and the non-binary people. Our results confirm that transgender people in Serbia are exposed to violence and discrimination in different life periods and different areas of life, that they do not feel safe and often hide their gender identity. When it comes to medical gender affirmation procedures, respondents are divided between rating them as satisfactory and non-satisfactory. As the main priorities, they see regulation of hormone shortage, training of health providers on working with transgender and non-binary people, individualization of the treatment, and decentralization of services. They also voiced out the need for psychological support, which can be regarded as the invitation to mental health experts to better understand specific aspects of everyday lives of their transgender clients.
Keywords: transgender; gender identity; discrimination; violence.; transspecific health care